The Extent Of Architect's Integration Into The Design & Build Construction Process In Peninsular Malaysia. - Tan , Seong Yeow (2002)

(untitled)
The Design and Build procurement method has been credited as a viable instrument to produce building delivery efficiency in the construction industry. This is especially so during a economic recession where the Government needs to inject equity into the national economy through the building of civil and institutional buildings. Its fast track approach helps to release monies to the various parties in the industry but its main beneficiary is the contractor who .becomes the leader of the team. The architect who traditionally leads the building team has been sidelined to a mere designer with minimal involvement in the contract administration. Claims that the architect is relieved of major liabilities to be borne by the contractor is a faf!acy that needs to be exposed. The use of novation could be explored as a means for the architect to play a more integrated role in the D&B process. Kaedah perolehan 'Design and Build' telah diiktirafkan sebagai satu cara untuk meningkatkan produktiviti industri pembinaan. Ini memandangkan usaha kerajaan untuk mengalirkan ekuiti kedalam ekonomi negara melalui projek-projek pembinaan bangunan sivil dan institusi. Sifat 'fast track' dalam kaedah ini dapat membantu kedudukan kewangan ahli-ahli industri terutamanya para kontraktor yang menjadi pemimpin pasukan pembinaan didalam kaedah perolehan ini. Para akitek yang secara tradisinya menjadi ketua pasukan pembinaan, telah disisirkan perananya, menjadi pereka semata-mata dengan pembabitan minima didalam pengurusan kontrak. Kononnya bahawa akitek dapat meringkan beban Iiabilitinya kepada kontraktor adalah merupakan satu persepsi yang silap. Walau bagaimanapun, penggunaan 'novation' perlu dijelajahi sebagai satu kaedah untuk akitek memainkan peranan yang lebih mendalam bagi kaedah D&B.